Hi , multiply equation by
Hey guys im stuck on an equation and just cant seem to get the right answer. I know there must be something wrong with my working. Could someone please show me how you multiply out the denominator to solve this equation.
1+ 6/x-1 = 1/x+1
Thank you in advance for any help.
Thank you for your quick reply. I tried that and still cant seem to get the correct answer. I know the answer because I have checked and I cant even work backwards to get it. Ill show my working out and maybe someone will know where im going wrong..
1+ 6/x-1 = 1/x+1
1+6(x+1) = (x-1)
1+6x+6-x-1 = 0
5x+6 = 0
)
(
)
But the proper answer is= X^{2}+5x+6=0
x=-3 & -2
I cant seem to find where x^{2} came from.
In such cases go by the following algorithm.
Step-1: Multiply the equation be the LCM of the denominator which in this case is (x-1)(x=1)
.(x-1)(x+1)[ 1 + 6/(x-1) = 1/(x+1) OR x^2 -1 + 6(x+1) = (x-1)
Step 2: Simplify the equation
x^2 -1 + 6x+6 = x-1
x^2 -1 + 6x+6 -x+1= 0
x^2 + 5x+6 = 0
(x+3)(x+2) = 0
etc.